Mesenchymal stem cells enhance the oncolytic effect of Newcastle disease virus in glioma cells and glioma stem cells via the secretion of TRAIL. Issue 1 (December 2016) - Kazimirsky, Gila; Jiang, Wei; Slavin, Shimon; Ziv-Av, Amotz; Brodie, Chaya
Abstract Background Newcastle disease virus (NDV) is an avian paramyxovirus, which selectively exerts oncolytic effects in cancer cells. Mesenchymal stem cells (MSCs) have been reported to affect tumor growth and deliver anti-tumor agents to experimental glioblastoma (GBM). Here, we explored the effects of NDV-infected MSCs derived from different sources, on glioma cells and glioma stem cells (GSCs) and the mechanisms involved in their effects. Methods The glioma cell lines (A172 and U87) and primary GSCs that were generated from GBM tumors were used in this study. MSCs derived from bone marrow, adipose tissue or umbilical cord were infected with NDV (MTH-68/H). The ability of these cells to deliver the virus to glioma cell lines and GSCs and the effects of NDV-infected MSCs on cell death and on the stemness and self-renewal of GSCs were examined. The mechanisms involved in the cytotoxic effects of the NDV-infected MSCs and their influence on the radiation sensitivity of GSCs were examined as well. Results NDV induced a dose-dependent cell death in glioma cells and a low level of apoptosis and inhibition of self-renewal in GSCs. MSCs derived from bone marrow, adipose and umbilical cord that were infected with NDV delivered the virus to co-cultured glioma cells and GSCs. Conditioned medium of NDV-infected MSCs induced higher level of apoptosis in the tumor cells compared with the apoptosis induced by their direct infection with similar virus titers. These results suggest that factor(s) secreted by the infected MSCs sensitized the glioma cells to the cytotoxic effects of NDV. We identified TRAIL as a mediator of the cytotoxic effects of the infected MSCs and demonstrated that TRAIL synergized with NDV in the induction of cell death in glioma cells and GSCs. Moreover, conditioned medium of infected MSCs enhanced the sensitivity of GSCs to γ-radiation. Conclusions NDV-infected umbilical cord-derived MSCs may provide a novel effective therapeutic approach for targeting GSCs and GBM and for sensitizing these tumors to γ-radiation.